Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To determine which equation models the same quadratic relationship as the function [tex]\( f(x) = 2x^2 - 12x + 11 \)[/tex], we need to compare the given function with each of the possible answers in the expanded form.
Let's explore each option one-by-one:
### Option A: [tex]\( y = 2(x + 3)^2 - 7 \)[/tex]
First, we need to expand [tex]\( 2(x + 3)^2 - 7 \)[/tex]:
[tex]\[ 2(x + 3)^2 - 7 = 2(x^2 + 6x + 9) - 7 \][/tex]
[tex]\[ = 2x^2 + 12x + 18 - 7 \][/tex]
[tex]\[ = 2x^2 + 12x + 11 \][/tex]
### Option B: [tex]\( y = 2(x + 6)^2 + 2 \)[/tex]
Next, let's expand [tex]\( 2(x + 6)^2 + 2 \)[/tex]:
[tex]\[ 2(x + 6)^2 + 2 = 2(x^2 + 12x + 36) + 2 \][/tex]
[tex]\[ = 2x^2 + 24x + 72 + 2 \][/tex]
[tex]\[ = 2x^2 + 24x + 74 \][/tex]
### Option C: [tex]\( y = 2(x - 6)^2 + 5 \)[/tex]
Now, let's expand [tex]\( 2(x - 6)^2 + 5 \)[/tex]:
[tex]\[ 2(x - 6)^2 + 5 = 2(x^2 - 12x + 36) + 5 \][/tex]
[tex]\[ = 2x^2 - 24x + 72 + 5 \][/tex]
[tex]\[ = 2x^2 - 24x + 77 \][/tex]
### Option D: [tex]\( y = 2(x - 3)^2 - 7 \)[/tex]
Finally, let's expand [tex]\( 2(x - 3)^2 - 7 \)[/tex]:
[tex]\[ 2(x - 3)^2 - 7 = 2(x^2 - 6x + 9) - 7 \][/tex]
[tex]\[ = 2x^2 - 12x + 18 - 7 \][/tex]
[tex]\[ = 2x^2 - 12x + 11 \][/tex]
Upon expanding each equation, we find that Option D produces the same quadratic equation as [tex]\( f(x) = 2x^2 - 12x + 11 \)[/tex].
Therefore, the correct answer is:
[tex]\[ \boxed{D} \][/tex]
Let's explore each option one-by-one:
### Option A: [tex]\( y = 2(x + 3)^2 - 7 \)[/tex]
First, we need to expand [tex]\( 2(x + 3)^2 - 7 \)[/tex]:
[tex]\[ 2(x + 3)^2 - 7 = 2(x^2 + 6x + 9) - 7 \][/tex]
[tex]\[ = 2x^2 + 12x + 18 - 7 \][/tex]
[tex]\[ = 2x^2 + 12x + 11 \][/tex]
### Option B: [tex]\( y = 2(x + 6)^2 + 2 \)[/tex]
Next, let's expand [tex]\( 2(x + 6)^2 + 2 \)[/tex]:
[tex]\[ 2(x + 6)^2 + 2 = 2(x^2 + 12x + 36) + 2 \][/tex]
[tex]\[ = 2x^2 + 24x + 72 + 2 \][/tex]
[tex]\[ = 2x^2 + 24x + 74 \][/tex]
### Option C: [tex]\( y = 2(x - 6)^2 + 5 \)[/tex]
Now, let's expand [tex]\( 2(x - 6)^2 + 5 \)[/tex]:
[tex]\[ 2(x - 6)^2 + 5 = 2(x^2 - 12x + 36) + 5 \][/tex]
[tex]\[ = 2x^2 - 24x + 72 + 5 \][/tex]
[tex]\[ = 2x^2 - 24x + 77 \][/tex]
### Option D: [tex]\( y = 2(x - 3)^2 - 7 \)[/tex]
Finally, let's expand [tex]\( 2(x - 3)^2 - 7 \)[/tex]:
[tex]\[ 2(x - 3)^2 - 7 = 2(x^2 - 6x + 9) - 7 \][/tex]
[tex]\[ = 2x^2 - 12x + 18 - 7 \][/tex]
[tex]\[ = 2x^2 - 12x + 11 \][/tex]
Upon expanding each equation, we find that Option D produces the same quadratic equation as [tex]\( f(x) = 2x^2 - 12x + 11 \)[/tex].
Therefore, the correct answer is:
[tex]\[ \boxed{D} \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.